FEATURES OF THE MODERN CLINICAL COURSE OF CHRONIC HEART FAILURE - Qobiljonova Shaxnoza Rustamovna; Allambergenova Jasmina Ergashevna; Odilov Shohidbek Dilmurod O’g’li; Malikjonov Ulug’bek Ilhom O’g’li (Modern American Journals, 2025)
Relevance of the problem. Despite significant advances in the treatment of cardiovascular diseases, the prevalence of chronic heart failure (CHF) is not only not declining but is steadily increasing, with the growth in incidence resembling a non-communicable epidemic. The MONICA study, conducted on a large, unorganized population, showed a CHF prevalence of 2%. A study of city residents over 50 years of age found a CHF prevalence of up to 4%. In the EPOCHA-CHF population-based study, the increase in CHF prevalence by clinical criteria was more than 4%, especially in older age groups, reaching 9.7%.